Estimativa da área da folha e características morfométricas de Castanheira-do-Brasil no norte do estado do Mato Grosso - Bouvié, Luana (2017)
The Brazil nut seed is appreciated for its flavor and nutritional qualities as well as being a symbol of sustainable and strategic development for the Amazonian conservation. Thus, the knowledge of the environmental ecology in which the B. excelsa species is found is of great importance for detailed investigation of their ecophysiological interactions. In this context, the objective was to calibrate and validate models of estimation of leaf area of the species Bertholletia excelsa from linear measurements, in trees of different ages. For this purpose, 750 leaves were collected in Young Trees (AJ) and Adults (AA) (individuals with remnants of reproductive structures below the crowns, each tree being a repeat (Chapter 2) and To understand the influence of environmental changes on the architecture of adult trees of the Castanheira do Brasil (Bertholletia excelsa), the morphometry of populations in two ecologically distinct almond producing sites was characterized: native forest area (under low impact exploitation) and trees (Table 3). In order to calibrate the leaf area equations, the samples were divided into three classes by the frequency distribution of the AFR and the descriptive statistics of linear dimensions and leaf area were determined. Linear regressions were used, considering the real leaf area (AFR) as the dependent variable, and the linear dimensions as independent variables, with the Solver tool of Microsoft Excel, the adjusted coefficients of the equations were calculated. The performance of the models was evaluated through statistical indicators: MBE; RMSE and dw. The leaf area of Castanheira-do Brasil, in both young trees and adult trees, can be measured using the equations AF = (a1 * C * L) + a2; AF = α 1 * [(C * L) α b]; Who had an MBA of -2.0717 and -2.3176 cm²; RMSE of 14.3645 and 14.4092 cm and dw equal to 0.9999 for both. The species Bertholletia excelsa does not present foliar polymorphism. Measurements of the length and width at the center of the leaf are sufficient to estimate the area of the limbus. It is concluded that in the estimations based on a measure, the following equations apply: AF = (0.7705 * C * L) +1.8135; AF = (0.7544 * C * L) + 5.1624; AF = 0.7997 * [(C * L) = 0.9949] and AF = 0.9334 * [(C * L) = 0.9674]. And for morphometric characterization of morphometric matrices of the adult tree architecture of the Castanheira do Brasil (Bertholletia excelsa Humb. & Bonpl.). During the month of June of the year 2016, 100 matrices of B. excelsa were sampled in the southern region of Amazonia, inventoried in Floresta (FN) area (11 ° 34 'S, 94 ° 55 ° 17' W), area Exploited in 2002 according to the current principles of the Sustainable Forest Management Plan (PMFS - Decree No. 1.282 / 1994); And another hundred isolated trees in a planted area (AA). For each sample tree, the basal area (g), the crown projection area (APC), and the total height of the crown were measured. (IA), salience index (SI) and living space index (VFI). In the present study, the spatial distribution of the spatial variability of the spatial distribution of the spatial variability of the spatial variability of the spatial distribution of spatial variability was studied. The age of the trees was indirectly and non-destructively categorized according to the frequency distribution of DAPs in each phytosociological condition. The descriptive statistics, variance analysis and the distribution curves were calculated. The stratification of the data in diametric classes to analyze the morphometric patterns was adequate, and a difference was found between the environmental conditions. The diameter at the chest height (168.47 cm) and the basal area (2,241 m²) are larger in the crop. The difference in the growth environment does not influence the height of the canopy; The mean crown diameter is higher in specimens found in the Forest (33.3), only when considering the older chestnut trees (with DBH greater than 1 m). The canopy diameter, regardless of tree age and environmental condition, is directly proportional to the stem diameter. The highest degree of slenderness (64.35, 39.54, 27.84 for classes 1, 2 and 3), comprehensiveness indexes (0.58, 0.65, 0.79 for classes 1, 2 and 3) , Living space indices (1253.35, 631.02 and 456.40 for classes 1, 2 and 3), and salience (34.42, 24.77 and 21.24 for classes 1, 2 and 3) , Occur in individuals grown in the forest environment. The survival rate is higher in Brazilians with smaller diameter (both), both in the forest environment and in the forest.